Handbook of properties of textile and technical fibres - Bunsell, A. R. (Textile Institute book series., 2018)
Handbook of Properties of Textile and Technical Fibres, Second Edition introduces tensile properties and failure and testing of fibers, also examining tensile properties and the failure of natural fibers, such as cotton, hemp, flax, agave, wool and silk. Next, the book discusses the tensile properties and failure of synthetic fibers, ranging from polyamide, polyester, polyethylene and carbon fibers. Chapters provide a general background of the fiber, including its manufacture, microstructure, factors that affect tensile properties and methods to improve tensile failure. With its distinguished editor and international contributors, this book is an important reference for fiber scientists, textile technologists, engineers and academics.